HemoglobinA1c Is a Risk Factor for Changes of Bone Mineral Density: A Mendelian Randomization Study - Ji, Xiaoxiao; Hong, Jianqiao; Qu, Zihao; Yang, Weinan; Wang, Yibo; Lin, Jiyan; Li, Congsun; Wang, Jie; Mou, Haochen; Shi, Mingmin; Zhou, Chenhe; Wang, Wei; et al. (Frontiers in Endocrinology, 2022)
Background: As a valuable blood glucose measurement, HemoglobinA1c (HbA1c) is of great clinical value for diabetes. However, in previous observational studies, studies on its effect on bone mineral density (BMD) have different results. This study aimed to use Mendelian randomization (MR) to assess the effect of HbA1c on bone mineral density and fracture risk, and try to further explore whether this association was achieved through glycemic or non-glycemic factors. Methods: Take HbA1c measurement as exposure, and BMD estimated from quantitative heel ultrasounds (eBMD) and bone fractures as outcomes. Two-Sample MR Analysis was conducted to assess the causal effect of HbA1C on heel BMD and risk fracture. Then, we performed the analysis using two subsets of these variants, one related to glycemic measurement and the other to erythrocyte indices. Results: Genetically increased HbA1C was associated with the lower heel eBMD (odds ratio [OR] 0.91 [95% CI 0.87, 0.96] per %-unit, P = 3 × 10−4(IVW)). Higher HbA1C was associated with lower heel eBMD when using only erythrocytic variants (OR 0.87 [0.82, 0.93], P=2× 10−5(IVW)); However, when using only glycemic variants, this casual association does not hold. In further MR analysis, we tested the association of erythrocytic traits with heel eBMD. Conclusion: Our study revealed the significant causal effect of HbA1c on eBMD, and this causal link might achieve through non-glycemic pathways (erythrocytic indices).